Cardiac Output Monitoring by Pulse Contour Analysis, the Technical Basics of Less-Invasive Techniques - Grensemann, Jörn (Frontiers in Medicine, 2018)
Routine use of cardiac output (CO) monitoring became available with the introduction of the pulmonary artery catheter into clinical practice. Since then, several systems have been developed that allow for a less invasive CO monitoring. The so called “non-calibrated pulse contour systems” (PCS) estimate CO based on pulse contour analysis of the arterial waveform, as determined by means of an arterial catheter without additional calibration. The transformation of the arterial waveform signal as a pressure measurement to a CO as a volume per time parameter requires a concise knowledge of the dynamic characteristics of the arterial vasculature. These characteristics cannot be measured non-invasively and must be estimated. Of the four commercially available systems, three use internal databases or nomograms based on patients’ demographic parameters and one uses a complex calculation to derive the necessary parameters from small oscillations of the arterial waveform that change with altered arterial dynamic characteristics. The operator must ensure that the arterial waveform is neither over nor under dampened. A fast-flush test of the catheter-transducer system allows for the evaluation of the dynamic response characteristics of the system and its dampening characteristics. Limitations to PCS must be acknowledged, i.e. in intra-aortic balloon-pump therapy or in states of low or high systemic vascular resistance where the accuracy is limited. Nevertheless, it has been shown that a perioperative algorithm-based use of PCS may reduce complications. When considering the method of operation and the limitations, the PCS are a helpful component in the armamentarium of the critical care physician.